Emprego de óleos essenciais no controle de Frankliniella occidentalis (Pergande) (Thysanoptera, Thripidae) em Impatiens hawkeri - Uhdre, Renan Santos (2017)
In recent years, Brazil has been showing a constant increase about production of flowers and ornamental plants, in terms of diversity and quantity and quality. In this scenario, the culture of Impatiens hawkeri has been outstanding by your versatility. The same, however, is subject to the attack of insect-pests, being the tripes the main responsible for damages in the phase of flowering. These damages can be direct, due to the feeding of the insect or indirect, by inoculation of virus. In order to reduce use of pesticides for pest control, the efficacy of essential oils of the species Cymbopogon winterianus (citronella) and Rosmarinus officinalis (rosemary) at concentration of 3% applied on spraying plants of impatiens was evaluated. The insecticide abamectin (Vertimec® 18 EC) was also used as the commercial control standard. This work was carried out in greenhouse and complete randomized complete block design with 90 treatments, seven replicates, composed of three varieties of Impatiens hawkeri and six products (1 ? water; 2 - water + tween; 3 ? essential oil of rosemary; 4 - essential oil of citronella; 5 - essential oil of rosemary + citronella; 6 - abamectin). The products were applied only once time and evaluations were performed at 1, 2, 3 and 7 days after application. The variables responses were: height plant, stem diameter, flower color preference and number of thrips. The results of the evaluations were submitted to analysis of variance (F-test with ? 5%) and was used the Bartlett test at 1% error probability to verify the homogeneity among the variances to the through the SAS University Edition computational application. Significant post-F qualitative data were submitted to the Scott-Knott method clustering test (p <0.05) and regression analysis for quantitative data using the SISVAR 5.6 computational application. In the period of pest monitoring the taxonomic collection and identification of the thrips species found in the impatiens plants was carried out. It was found that Frankliniella occidentalis (Pergande) was the species of thrips prevalent in the samples; it was verified that only the treatment based on abamectin (Vertimec® 18 EC) showed efficiency in the thrips control; it was found that the essential oils of rosemary and citronella caused changes in the morphological aspects of plants